Analysis on Geometric Mathematics Textbooks for Grade 5 of Elementary Schools in Malaysia, China, and Indonesia - Alim, Jesi Alexander; Hermita, Neni; Wijaya, Tommy Tanu; Putra, Zetra Hainul; Talib, Corrienna Abdul; Fauza, Naila (Jurnal Pendidikan Progresif, 2022)
Analysis on Geometry Mathematics Textbooks for Grade 5 of Elementary Schools in Malaysia, China, and Indonesia.  Objectives: This research analyzes the differences in the geometry material presented to grade 5 students of elementary schools and determines the characteristics of the questions in mathematics textbooks. Methodes: The content analysis compared the geometry materials in the best mathematics textbooks widely used in grade 5 of elementary schools in Indonesia, Malaysia, and China. The analysis discussed several important points on geometry material, including sub-chapter, chapter content, and the presentation of practice questions. Findings: The results show that 66.36% of questions in the Indonesian textbook asked about knowing, 24.54% applying, and 0.09% reasoning. In the Malaysian textbook, 71.42% of questions asked focused knowing, 23.8% applying, and 4.76% reasoning. Furthermore, 49.6% of questions in the Chinese textbooks asked about knowing, 30.4% applying, and 20% reasoning. Conclusions: questions on knowing had the highest percentage in the Indonesian and Malaysian textbooks but balanced in Chinese. Keywords: mathematics, geometry, indonesian, malaysian, Chinese.DOI: http://dx.doi.org/10.23960/jpp.v12.i1.202210